FOSTERING STUDENTS’ CLAUSE AWARENESS ON READING: The Exploration on Transitivity System - Basori, Muchamad Adam; Wiranegara, Dian Arsitades (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2016)
The opportunity to help students easily read English texts by observing content of the texts, which are construed in students’ world experience into limited set of processes type: material, mental, relational, behavioural, verbal and existential has confirmed the necessity of combating misunderstanding clause meanings (process, participant, circumstance). The notion of reading a text is manifested in the processes from a step-by-step lexico-grammatical analysis to contextual description, which are realised as a configuration of transitivity functions which represent the process, the participant situation, the attributes assigned to participant, and the circumstances associated with the process. These are typical patterns of lexico-grammatical realization. This study will examine the transitivity analysis, which provides the recognition of clause awareness on reading English texts. The implication of clause awareness on reading English texts based on the processes is to describe certain feeling, thought, and perception (perceiving through five senses) and creating an ordered technical vocabulary and way of classifying the world.